New Igołomia? The Second Seminar of Young Researchers on Prehistory in Biskupin - Płaza, Dominik; Szubski, Michał (Acta Archaeologica Lodziensia, 2018)
The Second Young Prehistoric Researchers Seminar in Biskupin took place from 6 till 8th of April 2018. The meeting was organized by The Doctoral Students Research Group from Cardinal Wyszyński University, The Students Research Group from Adam Mickiewicz University and The Archaeological Museum in Biskupin. The Konrad Jażdżewski Foundation for Archaeological Research were the patrons of the Seminar. The Biskupin Seminar is exceptional because each presentation was followed by long discussions with many questions and suggestions. The main idea of that meeting is integration of another generation of archaeologists who are interested in stone age research and giving them a chance for comfortable for a presentation of their doctoral, MA or BA thesis and their research vision in a comfortable atmosphere which guarantees a warm and positive reception. We would like to invite you all to the next seminar in 2019.